Group 14 elements in the Cmcm phase with a direct band structure for photoelectric application. (1st January 2023) - Fan, Qingyang; Sun, Yichao; Zhao, Yingbo; Song, Yanxing; Yun, Sining
Abstract: This work presents two novel group 14 element allotropes, o C24 Si24 and o C24 Ge24, and the physical properties of o C24 C24, o C24 Si24, and o C24 Ge24 are studied in detail by means of first-principles calculations. The mechanical stability, dynamic stability, and thermodynamic stability of o C24 Si24 and o C24 Ge24 are proven by the elastic parameters, phonon spectrum, and relative enthalpy, respectively. According to the B / G value, all o C24 C24, o C24 Si24, and o C24 Ge24 are brittle materials. By analysing the directional dependence of Young's modulus, it is clear that o C24 Si24 possesses the largest mechanical anisotropy. From the electronic properties, it can be concluded that o C24 Si24 is a semiconductor material with a direct band gap of 1.047 eV, which suggests that o C24 Si24 may be suitable to make solar cells. More importantly, the light absorption ability of o C24 Si24 is stronger than that of diamond Si in the visible light region. In addition, the κ min of o C24 Si24 and o C24 Ge24 have better thermal conductivity, indicating that o C24 Si24 and o C24 Ge24 have great application potential in solar cells, optoelectronic devices and other microelectronic devices.